2005
DOI: 10.1051/forest:2005006
|View full text |Cite
|
Sign up to set email alerts
|

Site quality equations for Pinus sylvestris L. plantations in Galicia (northwestern Spain)

Abstract: -Difference equations derived on the basis of the Sloboda and McDill-Amateis differential functions, and from the integral form of the Bertalanffy-Richards, Korf and Hossfeld growth functions were used to model the dominant height growth of Scots pine (Pinus sylvestris L.) in Galicia (north-western Spain). Data from stem analysis and permanent sample plots were combined and used for fitting. Both numerical and graphical analyses were used to compare alternative models. The cross-validation approach was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 36 publications
1
16
0
10
Order By: Relevance
“…The dominant height-age relationship was described using models based on those of Schumacher (1939) and Chapman-Richards (Richards, 1959) that have proved to be efficient for determining the site indexes of various conifer species (Castillo et al, 2013;Diéguez, Álvarez, Barrio, & Rojo, 2005; Vargas-Larreta, Álvarez-González, Corral-Rivas, & Aguirre-Calderón, cualquiera de los métodos descritos anteriormente ha generado gran polémica; sin embargo, en los últimos años se le ha dado mayor importancia al desarrollo de funciones de índices de sitio dinámicas con curvas polimórficas dependientes de un parámetro, pues se considera que las tendencias de las curvas modelan con mayor precisión el crecimiento en altura de los árboles (Goelz & Burk, 1992;Ker & Bowling, 1991;Payandeh & Wang, 1994).…”
Section: Models To Determine the J Deppeana Site Indexunclassified
See 1 more Smart Citation
“…The dominant height-age relationship was described using models based on those of Schumacher (1939) and Chapman-Richards (Richards, 1959) that have proved to be efficient for determining the site indexes of various conifer species (Castillo et al, 2013;Diéguez, Álvarez, Barrio, & Rojo, 2005; Vargas-Larreta, Álvarez-González, Corral-Rivas, & Aguirre-Calderón, cualquiera de los métodos descritos anteriormente ha generado gran polémica; sin embargo, en los últimos años se le ha dado mayor importancia al desarrollo de funciones de índices de sitio dinámicas con curvas polimórficas dependientes de un parámetro, pues se considera que las tendencias de las curvas modelan con mayor precisión el crecimiento en altura de los árboles (Goelz & Burk, 1992;Ker & Bowling, 1991;Payandeh & Wang, 1994).…”
Section: Models To Determine the J Deppeana Site Indexunclassified
“…The expression of these statistics is as follows: otras coníferas; no obstante, este trabajo representa la primera aproximación de análisis de J. deppeana. La relación altura dominante-edad se describió empleando los modelos base de Schumacher (1939) y el de Chapman-Richards (Richards, 1959) que han demostrado ser eficientes para la determinación de índices de sitio de diversas especies de coníferas (Castillo et al, 2013;Diéguez, Álvarez, Barrio, & Rojo, 2005; Vargas-Larreta, Álvarez-González, Corral-Rivas, & Aguirre-Calderón, 2010). El Cuadro 1 presenta dichos modelos probados en sus expresiones ADA y GADA, a partir de las ecuaciones base.…”
Section: Analysis and Comparison Of Modelsunclassified
“…In addition, it can be included to project the growth of the species in a reliable way, as mentioned by Diéguez-Aranda et al (2005). This study's applicability is restricted to the local level (Diéguez-Aranda et al 2009) despite the high pressure of such equations demonstrated by Trincado and Leal (2006), a situation by which the tting of generalized height-diameter models, either traditionally or under the mixed-eects approach, is an alternative that extends the functionality of the information generated, reduces biases and better covers regional variability (Corral-Rivas et al 2014, Kulie²is et al 2014). Other similar works mention the goodness of t of such results in the collection of eld information and in the accuracy of the total height estimates to calculate the volume individually or by stand (Diéguez-Aranda et al , Vibrans et al 2015.…”
Section: Resultsmentioning
confidence: 99%
“…But the height curves generated with local allometric models are the most accurate in the estimates of forests or stands (Diéguez-Aranda et al 2009). Model 7, selected for being more stable, presents the smallest deviations when estimating the total height according to diameter at breast height, and according to Costas and Rodríguez (2003) it can be used reliably in estimating height and other derived variables such as the volume of the stands or for the characterization of the structure of the tree masses of this species, as well as for economizing on forest inventory costs (Trincado and Leal 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Average wood production is around 4 to 5 m 3 ha −1 year −1 , with wide site variations [4]. Such variability seems to be caused by structure, site quality, diseases and competition [7].…”
Section: Introductionmentioning
confidence: 99%